Long memory, breaks, and trends: On the sources of persistence in inflation rates - Saskia Rinke; Marie Busch; Christian Leschinski (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
The persistence of inflation rates is of major importance to central banks due to the fact that it determines the costs of monetary policy according to the Phillips curve. This article is motivated by newly available econometric methods which allow for a consistent estimation of the persistence parameter under low frequency contaminations and consistent break point estimation under long memory without a priori assumptions on the presence of breaks. In contrast to previous studies, we allow for smooth trends in addition to breaks as a source of spurious long memory. We support the fi nding of reduced memory parameters in monthly inflation rates of the G7 countries as well as spurious long memory, except for the US. Nevertheless, only a few breaks can be located. Instead, all countries exhibit signi cant trends at the 5 percent level with the exception of the US.
Keywords: C13; E58; 330; Spurious Long Memory; Breaks; Trends; Inflation; G7 countries